IMPORTANCE OF THE PROCEDURES MANUAL IN BUSINESS ADMINISTRATION - Ariel Santos Flores, Adolfo; Jasmín Núñez González, Andrea; Elizabeth Cubilla Acuña, Cyntia (Revista Gênero e Interdisciplinaridade, 2023)
In the current world where we find ourselves, companies have had to adapt to new changes, we know that currently many companies direct their efforts to generate profits, taking into account simply the amount of sales of goods or services. , neglecting the administration of its human, technological and even financial resources. Every company for the development of its activities executes substantive and adjective processes. The nouns that correspond to those of the company’s objective and the adjectives that refer to those that support the main management. What is detrimental is that executing them does not have written policies and procedures, which radically affects the result of the management and therefore its strategic objectives.